Robustness of using degree of match in performing analog multiplication with spin-torque oscillators. (September 2021) - Mazza, Luciano; Puliafito, Vito; Carpentieri, Mario; Finocchio, Giovanni
Highlights: Spin-transfer torque magnetic tunnel junction (STT-MTJ) for analog multiplication. Syncronization and degree of match in STT-MTJs. Energy efficient computing. Abstract: The multiplication operation is one of the most used, but also one of the most energy-expensive operations in digital systems. Here, we focus on a promising strategy to perform the analog multiplication which is based on the use of two coupled spin-torque oscillators (STOs) using the concept of Degree of Match (DOM). The study is based on the theory of non-linear auto-oscillators with negative damping universally used for STOs. The robustness of the DOM is assessed with respect to the variability and noise perturbances parameters.